Multimodal management of locally advanced rhabdoid tumour of the kidney in an adult - Goel, Ritesh (BMJ Case Rep, 2021)
Malignant rhabdoid tumours of the kidney (MRTK) are rare paediatric tumours known for their aggressive nature and early metastasis. However, MRTK in adults are even more rare with only a few cases reported in the literature. Herein, we report a case of 65-year-old woman with rapidly progressive left renal mass requiring en-bloc radical nephrectomy, splenectomy and distal pancreatectomy. Histopathology revealed a malignant rhabdoid tumour with characteristic histological and immunohistochemical findings with negative margins. To the best of our knowledge, this is the first reported case of aggressive surgical management of locally advanced MRTK. Despite surgery with curative intent, the patient developed early recurrence and started on tyrosine kinase inhibitor. Unfortunately, the patient expired after 8 months of surgery due to disease progression.